UPAYA MENINGKATKAN SPEAKING SKILL MELALUI METODE COMMUNITY LANGUAGE LEARNING PADA PEMBELAJARAN BAHASA INGGRIS KELAS IV SDN KELAPA DUA WETAN 02 - Aris Harja Kusuma; Herlina Usman; Susi Winarni (STKIP Subang, 2026)
This study aimed to improve students’ English speaking skills through the implementation of the Community Language Learning (CLL) method in Class IV-B of SDN Kelapa Dua Wetan 02. Preliminary observations revealed that English instruction was still teacher-centered, resulting in low speaking performance among students. They tended to be passive, lacked confidence, and were reluctant to speak English due to fear of making mistakes. Consequently, their ability to pronounce vocabulary, construct simple sentences, and communicate orally had not developed optimally. This classroom action research employed four stages: planning, action, observation, and reflection. The study was conducted in two cycles, with three meetings in each cycle. The findings indicated a significant improvement in students’ speaking skills from Cycle I to Cycle II. In Cycle I, teacher activity reached 80% and student activity reached 85%, while 75% of students (24 out of 32) achieved the minimum mastery criterion of 70, which did not meet the predetermined success indicator of 80%. Therefore, improvements were made and the research was continued to Cycle II. In Cycle II, teacher activity increased to 88.9% and student activity reached 88%, while speaking skill mastery improved to 87.5% (28 out of 32 students), exceeding the success indicator. Based on these results, it can be concluded that the implementation of the Community Language Learning method effectively improved the English speaking skills of Class IV-B students at SDN Kelapa Dua Wetan 02.